Uma história da sífilis na cidade de Manaus: prostituição, controle e tratamento (1922-1934) - Odia, Mariana Mariano de Oliveira (Universidade do Vale do Rio dos Sinos, 2020)
This paper, entitled A History of Syphilis in Manaus: Prostitution, Control and Treatment (1922-1934), aims to analyze the fight against venereal diseases in Manaus, Amazonas, at the beginning of the twentieth century, mainly from the action of the Sanitation and Rural Prophylaxis Service of the State of Amazonas - SSPREAm. In particular, we will focus on combating syphilis in its relation to prostitution by investigating the medical discourse on the disease and their view of the link between prostitution and syphilis, as well as the proposed forms of control and treatment. The sources used were mainly medical reports from Doctor Samuel Uchôa, director of SSPREAm and the Book of Hygienic Inspection of the Merit in the State of Amazonas. The usage of these sources has convinced us of the role of this doctor, whose performance was fundamental in the question of perceptions and treatments for venereal diseases in Manaus. The analysis of the Book of Inspection of Harmfulness, maintained by SSPREAm, also made it possible to understand the social experiences of prostitution in Manaus and to discuss issues related to the sexuality and health of women involved in this activity in the city of Manaus during this period. The research therefore fits into the themes of the History of Public Health and the Sociocultural History of Disease.
Keywords: Sífilis; Manaus/Amazonas; Prostituição; Samuel Uchôa; Saúde pública; Syphilis; Prostitution; Public health; ACCNPQ::Ciências Humanas::História